The research of communication barriers of national and civic self-identification - Оstapenko, Iryna (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2017)
The article is devoted to the problem of of the impact of communicative barriers on the process of national and civic self-identification of youth.The author analyzed main approaches to study of the self-identification, the peculiarities of national and civic identity, as well as the role of communication barriers in national and civic self-identification of youth and also presented the results of empirical research and identified main types of communication barriers of national and civic self-identification of students. According to research results author defined that among com- munication barriers of national self-identification are dominate content-operational barriers, but individual psychological and social barriers are less there. Among communication barriers of civic self-identification are dominate individual psychological barriers, but content-operational barriers and social barriers are less there.
Keywords: national self-identification; civic self-identification; communication barriers; identity